2014
DOI: 10.3126/ijasbt.v2i4.11219
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of Antioxidants and Antihyperglycemic Effect of Barleria cristata leaves in Streptozotocin- Induced Diabetic Rats

Abstract: Objective: Many new bioactive drugs isolated from plants having hypoglycaemic effects showed anti diabetic activity equal and sometimes even more potent than known oral hypoglycaemic agents. In this present study, designed to evaluate antihyperglycermic and antioxidants effect on ethanolic leaf extracts Barleria cristata (EtBc) in streptozotocin-induced diabetic rats at dose level 400mg/kg body weight for the treatment of 45 days. Method and materials: The experimental rats were randomly divided into five grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The ethanolic leaf extract was also found to normalize the serum level of glycaemic profile such as insulin, C‐peptide, total haemoglobin and glycosylated haemoglobin levels as compared to that of control rats. This extract maintains the antioxidant (superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase and glutathione) levels and decreases the lipid peroxidation . In another attempt, Narmadha and Devaki revealed that ethanolic and aqueous leaf extract exhibited dose‐dependent increase in percentage inhibitory activity of α‐glucosidase enzymes, as well as α‐amylase when compared with a standard drug acarbose…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The ethanolic leaf extract was also found to normalize the serum level of glycaemic profile such as insulin, C‐peptide, total haemoglobin and glycosylated haemoglobin levels as compared to that of control rats. This extract maintains the antioxidant (superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase and glutathione) levels and decreases the lipid peroxidation . In another attempt, Narmadha and Devaki revealed that ethanolic and aqueous leaf extract exhibited dose‐dependent increase in percentage inhibitory activity of α‐glucosidase enzymes, as well as α‐amylase when compared with a standard drug acarbose…”
Section: Pharmacological Activitymentioning
confidence: 99%